2012
DOI: 10.3390/ijms13032769
|View full text |Cite|
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Treatment Is Associated with Prohibitin Expression in Renal Interstitial Fibrosis Rats

Abstract: This study was performed to investigate the association of prohibitin with renal interstitial fibrosis (RIF) lesion and to explore the association of all-trans retinoic acid (ATRA) treatment with prohibitin expression in RIF rats. Rats were divided into three groups: the sham operation group (SHO), the model group subjected to unilateral ureteral obstruction (UUO), and the model group treated with ATRA (GA). Renal tissues were collected at 14 and 28 days after surgery, and the relevant indicators were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…These results were similar to the results from our previous study in RIF rats. 6 RTEC injury plays a pivotal role in RIF and, therefore, the results suggest that ATRA attenuates the deposition of profibrotic components and might play a protective role against RIF lesion formation and progression. Currently, no reports from other research groups are available that assess the association of ATRA with RIFassociated renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were similar to the results from our previous study in RIF rats. 6 RTEC injury plays a pivotal role in RIF and, therefore, the results suggest that ATRA attenuates the deposition of profibrotic components and might play a protective role against RIF lesion formation and progression. Currently, no reports from other research groups are available that assess the association of ATRA with RIFassociated renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 The family includes prohibitin 1 (PHB1) and prohibitin 2 (PHB2), and several other multifunctional intracellular proteins, which all play important roles in the regulation of cellular proliferation, apoptosis and differentiation. 11 Our previous investigations 6 showed that ATRA treatment was associated with an increased expression of PHB in RIF rats, including renal tubular epithelial cells (RTEC). RTEC are polarized cells that constitute the predominant cell type within the tubulointerstitium, and play a critical role in normal kidney function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed the anti-inflammatory and anti-oxidative properties of Phb (21)(22)(23)30). Is there a relationship between clinical, laboratory, endoscopic, and histological activities of UC and Phb?…”
Section: Discussionmentioning
confidence: 99%
“…Phb-2 and Slp-2 are structural proteins located in cellular membranes, especially in the mitochondrial inner membrane. Besides anti-inflammatory and anti-oxidative properties, Phb has also been shown to have anti-fibrotic activity in experimental cirrhosis and renal fibrosis (21)(22)(23). Slp-2 is a regulatory protein that provides the binding of Phb and other proteins to cardiolipin for optimal assembly of oxidative enzyme complexes in mitochondria (24).…”
Section: Discussionmentioning
confidence: 99%